Deutsch: Geschichte und Gegenwart - Daga Portillo, Rocio (NomoK@non, 2024)
The Dhimma status, the status of non-Muslim living in Muslim territory, was not an invention of Islam, but had historical roots in the Byzantine and Persian empires. It was the solution to keep other peoples within the territory of Islam, in the context in which religion had taken over the role of “citizenship” - as in Byzantine Empire -. Due to the historical character of the Dhimma Status, a new parameter can be considered to establish a better relationship between Muslims and Non-Muslims of Islamic territory. Today the Dhimma status no longer exists, but written and unwritten laws of the Dhimma Status are still present, such as the prohibition to express the faith in public, a necessary permission from the country's president to build churches and the prohibition of a non-Muslim of holding high offices. Due to the uniformity of the law system in the Nation-states, non-Muslims are now under Islamic law in cases where they traditionally should have not been, such as the case of the prohibition of adopting a child or the Islamic inheritance law that discriminates against women. Even if Islamic law, Sharia law, has not been applied in the majority of Islamic countries for a century, except in relation to personal matters, inheritance law and family law, since the 80s of the 20th. century, medieval regulations have often been taken up again by extremist groups and applied. The status of non-Muslims, abolished since the mid-19th century, is looming on the horizon as extremist groups - a minority - again advocate it. Nonetheless, Islamic law, Sharia law, is not just law, it is also ethics and instructions for right behavior, ritual practice, and a way of relationship with God - through prayer and fasting. There are commonalities among the monotheistic religions, and this should be taken into account.